Efektfitas Kepemimpinan Demokratis Kepala Sekolah Dasar di Kota Lubuklinggau Dalam Meningkatkan Partisipasi Guru - Donni Pestalozi; Agusni Effendi; Ahmad Gawdy Prananosa; Benni Arianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effectiveness of democratic leadership of elementary school principals in Lubuklinggau City in increasing teacher participation. The research method used was a qualitative approach with phenomenology. The research subjects consisted of principals, teachers, school staff, and the school committee. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis used the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results show that principals implement democratic leadership by prioritizing openness, two-way communication, dialogue, and deliberation in decision-making, and involving teachers, staff, and the school committee in resolving various school issues. This leadership implementation was able to increase active teacher participation in school planning, implementation, and development. In conclusion, the principal's democratic leadership is effective in increasing teacher participation and supporting the creation of a school climate conducive to school progress. Keywords: Democratic Leadership, Principal, Teacher Participation, Elementary School